DESIGN AND IMPLEMENTATION OF HEART RATE MONITORING SYSTEM USING WIRELESS TECHNOLOGY - MOHD AZHAR, MUHAMMAD AFHAM (Universiti Teknologi Petronas, 2013)
Heartbeat rate changes depend on what someone is doing. Heartbeat rate monitoring system is the system that measures the number of heartbeat in a certain period of time. Wireless heartbeat monitoring system is a system where the heartbeat of any person can be monitored at one point but the subject is at another point without using any wires. The heartbeat is monitored wirelessly from object or it is monitored from a certain distance from the local host or end user. This enables the end user to have constant monitoring of object in real time situation. The current wireless heartbeat monitoring system that is available in the market can measure heartbeat at a very minimal distance. This project is focusing on the wireless transmission of heartbeat at further distance than the conventional product shall provide with the usage of the current RF technologies.